The Correlation between the Gas Permeability of Concrete and its Compressive Strength - أبودرعه عصام; خيربك علي; مكيّة سماح (Latakia University Journal -Engineering Sciences Series, 2023)
Sustainability has become one of the main directions for to build buildings with a longer life in order to conserve resources and save effort and money, But there is a common belief that producing high quality and durable concrete is only related to its compressive strength, this criterion is certainly not the only indicator of quality and is not sufficient to guarantee long-term durability. Our completed research focused on studying the concrete air permeability and relation with compressive strength. The results of the permeability test (on circular discs with a height of 5 cm cut from cylindrical samples (30 * 15) cm by Cembureau device according to ASTM C 597 showed a clear decrease in values of the permeability coefficient when using concrete with high strengths compared to samples taken from normal strength concrete. The test results for concrete with a compressive strength (20 MPa) gave a permeability coefficient of (744 m2), And the permeability of C30 strength class concrete was about 1.3 times higher compare to C20 strength class concrete , while the permeability of C40 strength class concrete was about 2.7 times higher compare to C20 strength class concrete.